First breeding evidence of marbled duck (Marmaronetta angustirostris) in Libya. - (:unkn) unknown (My University, 2014)
The first evidence of breeding of Marbled Duck (Marmaronetta angustirostris) in Libya, North Africa, is reported. In June 2012, at Mallaha wetland, in Tripoli, Libya, two dead ducklings were found that were later genetically identified as Marbled Duck. This breeding evidence suggests that this and other duck species may breed elsewhere in Libya. Better knowledge on Libyan, and more generally on north African, waterbirds is needed to document the population size and the status of these species. Such information will be important to secure the future of threatened species, such as the Marbled Duck.
Keywords: African Research